Outcomes for 298 breastfed neonates whose mothers received ketamine and diazepam for postpartum tubal ligation in a resource-limited setting - Gilder, ME; Tun, NW; Carter, A; Tan, FFSL; Min, AM; Eh, H; Aye, P; Carrara, VI; Angkurawaranon, C; McGready, R (BioMed Central, 2021)
Background Anesthesia in lactating women is frequently indicated for time-sensitive procedures such as postpartum tubal ligation. Ketamine and diazepam are two of the most commonly used anesthetic agents in low resource settings, but their safety profile in lactating women has not been established. Methods Medical records of post-partum tubal ligations between 2013 and 2018 at clinics of the Shoklo Malaria Research Unit were reviewed for completeness of key outcome variables. Logistic regression identified presence or absence of associations between drug doses and adverse neonatal outcomes: clinically significant weight loss (≥95th percentile) and neonatal hyperbilirubinemia requiring phototherapy. Results Of 358 records reviewed, 298 were lactating women with singleton, term neonates. There were no severe outcomes in mothers or neonates. On the first postoperative day 98.0% (290/296) of neonates were reported to be breastfeeding well and 6.4% (19/298) had clinically significant weight loss. Phototherapy was required for 13.8% (41/298) of neonates. There was no association between either of the outcomes and increasing ketamine doses (up to 3.8 mg/kg), preoperative oral diazepam (5 mg), or increasing lidocaine doses (up to 200 mg). Preoperative oral diazepam resulted in lower doses of intraoperative anesthetics. Doses of intravenous diazepam above 0.1 mg/kg were associated with increased risk (adjusted odds ratio per 0.1 mg/kg increase, 95%CI) of weight loss (1.95, 95%CI 1.13–3.35, p = 0.016) and jaundice requiring phototherapy (1.87, 95%CI 1.11–3.13, p = 0.017). Conclusions In resource-limited settings ketamine use appears safe in lactating women and uninterrupted breastfeeding should be encouraged and supported. Preoperative oral diazepam may help reduce intraoperative anesthetic doses, but intravenous diazepam should be used with caution and avoided in high doses in lactating women.